2020
DOI: 10.1093/ehjci/ehaa946.0882
|View full text |Cite
|
Sign up to set email alerts
|

The association of digoxin with mortality in ischemic heart failure: a secondary analysis of the STICH trial

Abstract: Background Digoxin, one of the first treatments for symptoms of congestive heart failure (CHF), is currently used in the management of persistent CHF symptoms as well as for ventricular rate control in atrial fibrillation. Current guidelines suggest digoxin as an adjunct to optimal medical therapy for symptomatic improvement in CHF. However, the data regarding the effect of digoxin use on mortality continue to be conflicting. Purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In addition, a recent study indicated that digoxin therapy was associated with an increased risk of all-cause and cardiovascular death in patients with ischemic heart failure. 34 ) Two medication classes were positively associated with digoxin use, including diuretics and MRAs. Current HF guidelines suggest digoxin as an adjunct to medical therapy for HF r EF; thus, digoxin may have been additionally prescribed in HF r EF patients receiving diuretics or MRAs, indicating persistent symptoms.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, a recent study indicated that digoxin therapy was associated with an increased risk of all-cause and cardiovascular death in patients with ischemic heart failure. 34 ) Two medication classes were positively associated with digoxin use, including diuretics and MRAs. Current HF guidelines suggest digoxin as an adjunct to medical therapy for HF r EF; thus, digoxin may have been additionally prescribed in HF r EF patients receiving diuretics or MRAs, indicating persistent symptoms.…”
Section: Discussionmentioning
confidence: 97%